2022
DOI: 10.3389/fonc.2022.1047215
|View full text |Cite
|
Sign up to set email alerts
|

A review of deep learning-based deformable medical image registration

Abstract: The alignment of images through deformable image registration is vital to clinical applications (e.g., atlas creation, image fusion, and tumor targeting in image-guided navigation systems) and is still a challenging problem. Recent progress in the field of deep learning has significantly advanced the performance of medical image registration. In this review, we present a comprehensive survey on deep learning-based deformable medical image registration methods. These methods are classified into five categories:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 146 publications
0
18
0
Order By: Relevance
“…Recent progress in the field of deep learning may be an approach capable of mitigating the co-registration errors. 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent progress in the field of deep learning may be an approach capable of mitigating the co-registration errors. 23…”
Section: Discussionmentioning
confidence: 99%
“…Thus, precise co‐registration is crucial to take full advantage of the MRWC‐based method. Recent progress in the field of deep learning may be an approach capable of mitigating the co‐registration errors 23 …”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional medical image registration methods, the greatest contribution of DL in medical image registration is to resolve the problem of slow medical image processing. 27 Eppenhof and Pluim 29 studied a CNN-based deformable registration algorithm and compared it with traditional algorithms. Their results showed that the registration speed of DL networks is hundreds of times that of traditional registration methods, with an average of 0.58 + 0.07s.…”
Section: Implementation Areamentioning
confidence: 99%
“…In recent years, DL, especially CNN, has achieved good results in medical image processing, and medical registration research has developed rapidly. 27 The 2 main types of existing medical image registration methods are gray-scale-based methods and featurebased methods. The primary steps of image registration include geometric size change, combined image change, image similarity measurement, iterative optimization, and interpolation process.…”
Section: Implementation Areamentioning
confidence: 99%
“…neuro-/radiation oncology [ 5 ]. Their capability for the deformable registration task has been increasingly investigated in different medical image modalities [ 6 ]. In these methods, in contrast to classical ones, deformable registration is defined as a parametric function.…”
Section: Introductionmentioning
confidence: 99%